Economic Relations Between Mexico and the European Union: Their Recent Evolution - Chacón, Mario (Revista Mexicana de Política Exterior, 2022)
This essay examines the recent evolution, and the actual state, of economic relations between Mexico and the European Union (EU). It is divided into six sections. The first analyzes the profound process which is Mexico's commercial aperture. The second and third sections analyze the evolution and actual state of commercial relationships and investment between Mexico and the EU. The fourth section focuses on a specific commercial problem, whose accentuation is likely: the difficulty that Mexican exports face in the European market, which is restricted to those countries with preferential access. The fifth section emphasizes the opportunity to create a privileged relationship among Mexico and the EU which stems from the coincidence between the Mexican need to deepen its commercial ties with the EU, and the European interest in our Nation. The sixth and final section points out that, even if a new Framework Accord were to be signed, this would not preclude the establishment of parallel strategies to permit an improved exploitation of the Accord now in force with the EU.